2009
DOI: 10.1158/0008-5472.sabcs-3037
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ER-a36, a novel variant of estrogen receptor a, and resistance to tamoxifen treatment in breast cancer.

Abstract: #3037 Background: Recently, a 36 kDa variant of estrogen receptor a (ER-a66), ER-a36, has been identified and cloned. ER-a36 predominantly localizes on the plasma membrane and in the cytoplasm and mediates a membrane-initiated “nongenomic” signaling pathway. In this study, we investigated the association between ER-a36 expression and tamoxifen resistance in breast cancer patients.
 Methods: ER-a36 protein expression in tumors from 710 breast cancer patients with a median follow-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 0 publications
8
63
0
1
Order By: Relevance
“…Recent studies have indicated that the efficacy of endocrine therapy cannot be simply explained by the expression levels of ERα, but may be determined by the expression profiles of both ERα and ERβ, as well as their various splice variants (14,21,24,25). Furthermore, to understand the meaning of the demonstrated change in ERα-36 expression induced by BMP2 in breast cancer cells, additional research should be carried out to determine whether the ERα-36 reported in the present study is the same as that reported by Wang et al (21).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the efficacy of endocrine therapy cannot be simply explained by the expression levels of ERα, but may be determined by the expression profiles of both ERα and ERβ, as well as their various splice variants (14,21,24,25). Furthermore, to understand the meaning of the demonstrated change in ERα-36 expression induced by BMP2 in breast cancer cells, additional research should be carried out to determine whether the ERα-36 reported in the present study is the same as that reported by Wang et al (21).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, subtle differences in ER conformations caused by (1) interaction with different ligands interacting with different co-activators or co-repressors within the cell; 50 (2) the existence of spliced receptor variants such as ER36 51,52 or ER46; 53 (3) recruitment of co-regulators by the orphan nuclear ERRa in a ligand-independent manner, 54-56 thus decreasing their availability for interaction with remaining ERs in some cell types but not others; (4) presence of different molecular chaperones such as FKBP51, FKBP52, and Cyp40, which may be incorporated in the inactivated ER complexes from the different cell types; 57,58 or simply, (5) that some of the responses are not ER-mediated responses. In the case of differences between human breast cancer cell lines MCF-7 and MDA-MB-231, differences had been explained by the role of the ERa46 isoform in cellular proliferation.…”
Section: Figmentioning
confidence: 99%
“…The presence of ER variants was also hypothesized to have a role in endocrine resistance. A reduced response to endocrine therapy has been associated with the presence of a new truncated variant of ER, ER36, in addition to the full-length receptor (Shi et al, 2009). …”
Section: Alterations In Er Expression or Functionmentioning
confidence: 99%